The implementation of Pendidikan Khas Kejogjaan in strengthening secondary school students' character - Sutrisna Wibawa; Suwarna; Rony Kurniawan Pratama; Yatun Romdonah Awaliah; Farid Setiawan (LPMPP Universitas Negeri Yogyakarta, 2026)
This study examines the implementation profile of Pendidikan Khas Kejogjaan (PKJ), a culturally grounded character education programme operating in pilot secondary schools across the Special Region of Yogyakarta. Researchers deliberately frame our inquiry around the implementation level rather than causal effectiveness, since the cross-sectional design researchers used cannot establish that students' character changed because of PKJ. Data were gathered from 150 senior and vocational high school students selected from twelve pilot schools through multistage sampling, combining purposive selection of schools with proportional random selection of students. A 102-item questionnaire (Cronbach's α = 0.93) was used to measure three implementation dimensions: philosophy, cultural values, and cultural atmosphere. Descriptive statistics showed a mean of 4.1361 for the philosophical dimension, 4.0433 at the cultural-values dimension, and 3.9289 at the atmosphere dimension. Pearson correlation analysis revealed strong and significant correlations among the three dimensions (r = 0.716 to 0.880, p < 0.01). The lower atmosphere score, paired with the higher score for cognitive culture (4.1133) than for behavioural (3.8467) and material cultures (3.8271), suggests that PKJ is currently more prominent in symbols and signage than in everyday habituation and material environments. Researchers argue that the trilogy of hamemayu hayuning bawana, sangkan paraning dumadi, and manunggaling kawula Gusti has been internalised at the level of recognition; however, the gap between symbol and practice remains a critical area for further policy work. The study provides a baseline framework of PKJ implementation upon which future longitudinal and comparative designs can build.